The Central Authority of the Republic of Indonesia’s Attorney General’s Office in Handling Forest Destruction Cases - Setyowati, Sulis (LifeSciFi, 2025)
This study aims to analyze the implementation of the authority of the Republic of Indonesia Prosecutor's Office in handling criminal cases of forest destruction through a multidoor approach, as well as to examine the application of the principle of substantive justice in prosecution practices based on the Palembang District Court Decision. The method used is applied normative legal research with a statutory approach, a case approach, and a conceptual approach. Secondary data was obtained through documentary studies and analyzed qualitatively descriptively. The results of the study indicate that the multidoor approach is applied in law enforcement against a series of criminal acts of forest destruction because it is related to natural resources and the environment which are regulated by various regulations. Furthermore, the Cassation Decision rejected the cassation request from Ir. Basta Siahaan, so that the Executing Prosecutor can implement the Appeal Decision which confirms the Palembang District Court Decision Number 1010/Pid.B/LH/2019/PN.Plg. In the decision, the defendant was sentenced to five years in prison and a fine of Rp2,000,000,000.00 with a subsidiary provision of four months in prison. This decision has fulfilled two-thirds of the Public Prosecutor's demands and demonstrates law enforcement efforts that pay substantive attention to the dimensions of legal and environmental justice.